Peningkatan Efisiensi Sistem Pemanasan dengan Penambahan Grid pada Perforated Burner - Widodo, Agung Sugeng (Jurnal Rekayasa Mesin, 2016)
Efficiency of a domestic gas stove depend on the kind of burner material and its configuration. In this study, a material in the form of a grid  has been inserted into combustion chamber  to modify flame characteristics. Grids made from stainless steel with different thickness were inserted between  burner and loading. Ceramic stove cover was used to prevent heat release from flame. To develop the term of efficiency of the system, many parameters were measured as energy from fuel, cover temperature and water temperature.  The results show that in certain fuel rate of 45 l/h, a heating system with  a grid of 5 mm has maximum efficiency of 58,8 %  indicate a differentiation of 5 % higher compared to the heating system with no grid. Grid material absorbs energy from combustion process, keep the temperature in  the combustion chamber remain high also induce turbulence upstream the grid surface causing fuel-air mixing  improved.